Mechanical and failure characteristics of fissured marble specimens under true triaxial compression: Insights from 3-D numerical simulations. (November 2020) - Zhang, Yongjun; Liu, Sijia; Kou, Miaomiao; Wang, Zaiquan
Abstract: In this study, 3-D particle-based discrete element methodology (DEM) is applied to investigate the mechanical and failure characteristics of fissured marble specimens in true triaxial compression with a new loading stress path. The new loading stress path is controlled by two loading parameters: the initial confining pressure σ 0 and the loading stress ratio b . In the numerical investigation, eighty-eight numerical fissured marble specimens are designed based on fissure arrangements, such as the fissure length 2 a, fissure inclination angle α, fissure ligament length 2 L, loading stress ratio b and initial confining pressure σ 0 . The mechanical properties, including the peak strength and effective elastic modulus, and the associated failure characteristics are quantitatively analyzed. Three different ultimate failure modes of the fissured marble specimens in true triaxial compression are summarized by numerical simulations. Numerical results indicate that the peak strength and equivalent elastic modulus are enhanced with increases in the loading stress ratio and initial confining pressure. It can be found from the numerical results that the influence of the initial confining pressures is more significant. The present numerical investigations on fissured marble specimens under true triaxial compression can provide a deep understanding of mechanical and failure behaviors of rock masses in underground construction.